Drivers of N2O emissions from natural forests and grasslands differ in space and time - Araujo, Patricia Ines; Piñeiro Guerra, Juan Manuel; Yahdjian, Laura; Acreche, Martin Moises; Alvarez, Carolina; Alvarez, C.R.; Costantini, Alejandro Oscar; Chalco Vera, Jorge Elías; De Tellería, J.M.; Della Chiesa, T.; Lewczuk, Nuria; Petrasek, M.; et al. (Springer, 2020)
Understanding the drivers of greenhouse gas (GHG) emissions is one of the most critical global environmental challenges to mitigate the increasing global temperature. Nitrous oxide (N2O) emissions are highly variable in space and time and are controlled by multiple proximal drivers, that is, those that affect N2O emissions directly and in short timescales, and distal or indirect drivers that influence emissions over long timescales. Here we present a quantification of N2O emissions in grasslands and forests throughout the Pampas and the Semiarid Chaco in Argentina and reveal distal and proximal drivers, analyzing them in both spatial and temporal models. We measured N2O emissions, soil and climate variables monthly in nine sites over two years. Mean annual temperature and the following soil properties: phosphorous availability, carbon:nitrogen ratio, clay and sand percentages were the main distal drivers controlling N2O emissions in the spatial model, while among proximal drivers, only soil nitrate contents were positively related to N2O emissions. When considering the seasonal variability of N2O emissions (temporal model), we found that emissions were positively related to proximal drivers, such as soil nitrate and soil temperature. Our results show that soil N2O emission drivers differ between spatial and temporal models in natural grasslands and forests, explaining up to 85 and 56% of variations in N2O emissions, respectively. Temperature increased N2O emissions in both spatial and temporal models; therefore, future global warming may increase background emissions from natural ecosystems with important positive feedbacks on the earth system warming.